The persistence of party : Ideas of harmonious discord in eighteenth-century Britain, by Max Skjönsberg (Cambridge University Press, 2021) - LIU, Antong (Institutional Knowledge at Singapore Management University, 2021)
In The Persistence of Party: Ideas of Harmonious Discord in Eighteenth-Century Britain, Max Skjönsberg offers a new intellectual history exploring the discussion of party politics in eighteenth-century Britain, focusing on a series of thinkers who heavily influenced one another’s views of parties and partisanship. Uncovering the ways in which the appreciation of party politics came about in the eighteenth century, Skjönsberg’s excellent book not only contributes to intellectual history but also offers us a new reason to think that the cure for the increasingly troubling political polarisation today may still need to include vibrant partisan competitions.